1999
DOI: 10.1207/s15328023top2601_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Multimedia and Traditional Approaches in Undergraduate Psychology Classes

Abstract: In this study, we compared the effectiveness of multimedia and traditional classes. Six instructors within the Department of Psychology taught 1 of 3 courses: human development, psychological statistics, or abnormal psychology. An instructor taught each course in either a multimedia or traditional classroom. Results showed that (a) the students in the multimedia and traditional classes did not differ on scholastic abilities prior to course enrollment, (b) students in the larger multimedia class averaged higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 7 publications
5
27
0
Order By: Relevance
“…These results are in line with the ones obtained by Amare (2006) and Erwin and Rieppi (1999), but opposite to those obtained by Moreno and Mayer (2002) and Blokzijl and Andeweg (2005).…”
Section: Number Of Wrong Answerssupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in line with the ones obtained by Amare (2006) and Erwin and Rieppi (1999), but opposite to those obtained by Moreno and Mayer (2002) and Blokzijl and Andeweg (2005).…”
Section: Number Of Wrong Answerssupporting
confidence: 82%
“…), so it is difficult to compare them, and furthermore, they reach contradictory conclusions. Thus, while Moreno and Mayer (2002) and Blokzijl and Andeweg (2005) point to the effectiveness of PowerPoint in the recall of the material presented in class, other studies have shown how students achieve better results in a teacher-centred class without a PowerPoint presentation (Amare, 2006;Erwin & Rieppi, 1999), or simply no significant differences are observed between the two groups studied (Apperson et al, 2006;Barlett & Strough, 2003;Susskind, 2008). Other studies (Savoy et al, 2009) have focused on the effectiveness of the recall of material depending on the kind of information presented (graphic or verbal), stressing that students recalled around 15% less verbal information when it was presented with PowerPoint.…”
Section: Introductionmentioning
confidence: 99%
“…Students can maintain this portfolio by themselves and teachers can monitor the process from their own workplace. Working with digital portfolios via Internet makes the questionnaires and the portfolios available at any time to fit curriculum needs and also resolves time and space constraints (Kieley 1996;Erwin and Rieppe 1999;Parlangeli et al 1999;Hara et al 2000). In this way new and flexible tools become available for actively working on the improvement of the quality of views on learning and to increase self-awareness, which is important in social work education (Ladyshewsky and Gotjamanos 1996) …”
Section: Practical Implicationsmentioning
confidence: 99%
“…Support for the effectiveness of multimedia instruction is mixed. Some research has documented better exam performance in psychology courses employing multimedia as opposed to traditional formats (Erwin & Rieppi, 1999;Smith & Woody, 2000). Other studies comparing the two methods of instruction did not find differences in students' grades and found limited differences in course evaluations (Brewster, 1996;Stoloff, 1995).…”
Section: West Virginia Universitymentioning
confidence: 99%